2011
DOI: 10.1016/j.vaccine.2010.11.079
|View full text |Cite
|
Sign up to set email alerts
|

Yellow fever 17D-vectored vaccines expressing Lassa virus GP1 and GP2 glycoproteins provide protection against fatal disease in guinea pigs

Abstract: Yellow Fever (YF) and Lassa Fever (LF) are two prevalent hemorrhagic fevers co-circulating in West Africa and responsible for thousands of deaths annually. The YF vaccine 17D has been used as a vector for the Lassa virus glycoprotein precursor (LASV-GPC) or their subunits, GP1 (attachment glycoprotein) and GP2 (fusion glycoprotein). Cloning shorter inserts, LASV GP1 and GP2, between YF17D E and NS1 genes enhanced genetic stability of recombinant viruses, YF17D/LASV-GP1 and -GP2, in comparison with YF17D/LASV-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 56 publications
0
54
0
6
Order By: Relevance
“…The same electroporation device was also successfully used in HIV-1 DNA vaccine human trials (Kopycinski et al, 2012;Vasan et al, 2011). Since previous studies (Bredenbeek et al, 2006;Guy et al, 2010;Jiang et al, 2011) with recombinant YFV-17D-based vaccines showed that anti-vector immunity was a minor concern during prime-boost immunization, a prime-boost vaccination regimen was adopted to further augment the immune responses. Nevertheless, in vivo delivery of YFV infectious DNA by electroporation failed to induce YFVneutralizing antibodies in HLA-A2.1 transgenic C57BL/6 mice, despite readily detectable CD8 + T-cell responses, whereas YFV-17D vaccination of BALB/c mice was reported to yield a balanced Th1-Th2 immune response (Franco et al, 2010).…”
Section: Dna-launched Yfv-17dmentioning
confidence: 99%
See 2 more Smart Citations
“…The same electroporation device was also successfully used in HIV-1 DNA vaccine human trials (Kopycinski et al, 2012;Vasan et al, 2011). Since previous studies (Bredenbeek et al, 2006;Guy et al, 2010;Jiang et al, 2011) with recombinant YFV-17D-based vaccines showed that anti-vector immunity was a minor concern during prime-boost immunization, a prime-boost vaccination regimen was adopted to further augment the immune responses. Nevertheless, in vivo delivery of YFV infectious DNA by electroporation failed to induce YFVneutralizing antibodies in HLA-A2.1 transgenic C57BL/6 mice, despite readily detectable CD8 + T-cell responses, whereas YFV-17D vaccination of BALB/c mice was reported to yield a balanced Th1-Th2 immune response (Franco et al, 2010).…”
Section: Dna-launched Yfv-17dmentioning
confidence: 99%
“…YFV-17D has also been successfully exploited as a vector for the expression of foreign T-cell or B-cell epitopes, as potential vaccine candidates against malaria (Bonaldo et al, 2002;Tao et al, 2005) or as therapeutic anticancer vaccine (McAllister et al, 2000). Moreover, recombinant YFV-17D viruses expressing heterologous antigens were proposed as bivalent vaccine candidates against Lassa virus (Bredenbeek et al, 2006;Jiang et al, 2011) or as alternative vaccine vectors for malaria (Stoyanov et al, 2010) and HIV (Franco et al, 2010;Van Epps, 2005). In vitro characterization demonstrated that these recombinant viruses were viable and could express both YFV and foreign proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…56,65,66 A similar approach was employed to improve the genetic stability of Lassa virus glycoproteins expressed by recombinant YF17D viruses in this genomic site. 67,68 Interestingly, a variant of this general methodology was described in the expression of the HIV clade B consensus Gag p24 sequence by the YF17D virus. In this case, the heterologous protein was directly expressed in frame with the YF E protein and fused to the single transmembrane anchoring segment of the Sindbis virus E2 protein.…”
Section: Expression Of Larger Fragments By the Yf17d Virusmentioning
confidence: 99%
“…Other studies confirmed the capacity of this YF E/NS1 viral platform to elicit a T cell-specific response against other antigens. 31,56,67,68,74,75 These results point to a need of optimization of vaccination regimens as well as an improvement of the YF E/ NS1 insertion platform immunogenicity, which should be considered since the yellow fever vaccine displays outstanding immunological properties as a human immunogen. Another possibility to exploit the expression of foreign proteins by the live-attenuated YF17D virus consists of the insertion of sequences into the C gene.…”
Section: Expression Of Larger Fragments By the Yf17d Virusmentioning
confidence: 99%